Etiology of hearing loss affects auditory skill development and vocabulary development in pediatric cochlear implantation cases. (1st April 2022) - Nishio, Shin-ya; Moteki, Hideaki; Miyagawa, Maiko; Yamasoba, Tatsuya; Kashio, Akinori; Iwasaki, Satoshi; Takahashi, Masahiro; Naito, Yasushi; Fujiwara, Keizo; Sugaya, Akiko; Takahashi, Haruo; Kitaoka, Kyoko; et al.
Abstract: Background: Cochlear implantation (CI) is an effective treatment for severe-to-profound hearing loss patients and is currently used as the standard therapeutic option worldwide. However, the outcomes of CI vary among patients. Aims/Objectives: This study aimed to clarify the clinical features for each etiological group as well as the effects of etiology on CI outcomes. Materials and methods: We collected clinical information for 308 pediatric cochlear implant cases, including the etiology, hearing thresholds, age at CI, early auditory skill development, total development, monosyllable perception, speech intelligibility and vocabulary development in school age, and compared them for each etiology group. Results: Among the 308 CI children registered for this survey, the most common etiology of hearing loss was genetic causes. The genetic etiology group showed the most favorable development after CI followed by the unknown etiology group, syndromic hearing loss group, congenital CMV infection group, inner ear malformation group, and cochlear nerve deficiency group. Conclusions and significance: Our results clearly indicated that the etiology of HL affects not only early auditory skill development, but also vocabulary development in school age. The results of the present study will aid in more appropriate CI outcome assessment and in more appropriate intervention or habilitation programs.